Tratamento combinado com reator tipo UASB e processos oxidativos avançados em efluente hospitalar - Santos, Mariana Azevedo dos (2022)
One of the great challenges for sanitation is the treatment of hospital wastewater, since it contains many recalcitrant substances, especially drugs that are excreted by the human body or improperly discarded, making the effluent an ideal environment for the proliferation of resistant bacteria. Brazil does not have its own legislation for the treatment of hospital effluents, nor does it standardize ideal conditions to treat this waste with domestic sewage, só the efficiency of the biological process in the ETEs can be the recalcitrance and toxicity that these contaminants can cause. The objective of this work is to collect effluent from a Hospital in the State of Paraná and apply the anaerobic process of sewage treatment with a UASB type reactor and advanced oxidative processes (POA) Photolysis and UV/H2O2. For an adequacy of the reactor with the hospital effluent, they were divided into 4 Steps. The first used 25% of hospital effluent, showing a COD removal of 78 mg L-1 O2, and volatile acids of 4126.8 mg L-1 Hac. Stage II and II obtained COD removal values of 91% and 83%, respectively. Stage IV with total hospital effluent feeding showed COD values of 180 mg L-1 O2 and total alkalinity of 4128 mg L-1. Regarding the oxidative processes that most generated good results were UV/H2O2 in post UASB effluents. On the other hand, Photolysis obtained COD values below 100 mg L -1 O2 after 120 minutes of reaction. The system using the GERMETEC reactor used 500 mg L-1 of H2O2 and with 225 minutes of reaction obtained a small removal of COD, from 180 mg L-1 O2 to 108 mg L-1 O2. As for the toxicity data, the hospital’s raw effluent showed a germination index with Lactuca Sativa seeds, with no significant effect, with a result of 45.9, while the post UASB effluent showed high germination rates (100%), along with the On-Line Photolysis process.